Mineralogical characterization and elementary sediment solid lake Yantac department Junín, province Yauli, Marcapomacocha district xy ray diffraction by x-ray fluorescence - Miramira, Biviano (2016)
The samples were taken along the shores of Lake JunínYantac - being one of the objectives identified mineral pollutants from human activities (livestock, agriculture, etc.), and others. According to the results obtained by analysis of X-ray diffractograms (XRD) made in the laboratory X-ray of, San Marcos, show the presence of phases of minerals from which the environment (clean natural sediments) and are calcium carbonate, silicon oxide, montmorillonite, calcite, dolomite, quartz, and analysis by X-ray fluorescence (XRF), made in the Peruvian Institute of Nuclear Energy (IPEN) determined the presence of elements such as Al, Si, K, Ca, Fe higher percentage (%).